Anxiety disorders in children and adolescents research, assessment, and intervention - Silverman, Wendy K.; Treffers, Ph. D. A. (Cambridge child and adolescent psychiatry, 2001)
Anxiety disorders are among the most prevalent mental health problems in childhood. In this timely book, an international team of psychiatrists and psychologists review the most recent theoretical and empirical developments in the field and indicate how these may inform research and clinical practice. Following a historical introduction, chapters review conceptual and management issues, including cognitive, neurobiological, learning and developmental processes, and the influence of the peer group and family. Phenomenology, classification and assessment are covered, as are clinical course, intervention and outcome, with attention to both pharmacological and psychosocial treatment approaches. For clinicians and researchers this is an authoritative guide to the understanding and assessment of anxiety disorders in the young, and will appeal to all mental health professionals involved with this age group